Pengajaran dan pembelajaran muhawarah di Sekolah Rendah Kebangsaan / Mohammad Khairul Rawi - Rawi, Mohammad Khairul (2012)
Arabic language is a very unique universal language. It is the only language that was recognized by our Almighty Allah S.W.T to be the language of The Quran. Since the birth of Arabic language, almost half of the world populations speaking the language. This language was not only used by the Arabs for spoken and daily activities, it is also learnt and spoken by the other races in the world. In learning the Arabic language as one of the branches of knowledge in the world, there were many techniques and methods that were invented. The purpose is to simplify the teaching and learning to who ever want to learnt it including primary students. Among this method was muhawarah method. Muhawarah was one of the communicative branches at the moment. It was seen as a practical method to the teacher to teach, and the students to study. The implementation is very simple followed by the rules that were done by the students themselves seen as to be very effective process to the teaching and learning of the Arabic language especially for Communication Arabic. Therefore, this research was done to show the effectiveness of this muhawarah method in helping the teacher and especially the students in understanding Arabic language subject. The studies that had been done here involved three schools in Klang district that were SK Sungai Kapar Indah, SK Meru, and SK Taman Klang Utama. The studies sample involved year 6 pupils, and the teachers that teaches Arabic language in three school mentioned above. The studies are seen very important as it can be used by teachers and pupils that studies Arabic language, whether in schools or higher institutions. Some of the methods that being used by researcher to gained data were by observation and review at the chosen schools. Other than that, libraries researches were also done to gather as much as information that can be used for the research purposed. Research outcome generally found that muhawarah method is among the good and effective in the process of teaching and learning the Arabic language especially in the primary school. To present this thesis, the researcher had divided into five main topics, that is introduction, literature review, research methodology, research outcome and closure. Each of this topic, the researcher will elaborate in detail what had the researcher got from this research. Hopefully this research will help those who loved the Arabic language to continue to learn it and help to expand it to the higher level, Insyaallah.